Analysis of Decision Fusion Detection in Wireless Sensor Network - et. al., Priyanka Jaiswal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The emerging technology of embedded system and internet of things crack great potential of the wireless sensor network. The deployment and feasibility of wireless sensor network applied underdisciplined process of the task. The major issue of sensor node deployment is an energy factor. The life of energy depends on the strength of signals during transmission and sensing of the sensor node. The major factor to impact the sensor node's life is a distance of target node, signal attenuation and model of propagation model. The continuous efforts of various authors proposed various models and system level algorithms for the efficient utilization of energy in a large number of sensor node deployment cases in case of random and knew sensor node environments. This paper presents the analysis of distributed detection of energy based on decision fusion factor based on different constraints function. Most algorithms applied the process of probability function to estimate the energy function in terms of detection and false detection. This paper focuses on already developed methods of detection elaborate in the survey. The validation of algorithms designs a wireless sensor network environment in MATLAB software and standard measure parameters and analysed algorithms' behaviours. Also, the study of comparative performance of all presented algorithms.